(3HQfGeL JYdje GdcHGQ ddQjajGJ (B: s (3OQGSI GdBKGQ h GdJecjf HeMGaXI GdLjRI (B/ s - (3egG RcQjG MSf eMeO MSfs; (3YRI JgGei GdHfOGQi (B: s; (3eMeO Mdei fhGQ (B: s ((3GdbGgQI (B: s (3egG RcQjG MSf eMeO MSf (B: s, 2020)
(3CUHM JYdje h Jecjf GdeQCI ef GdQcGFR GdCSGSjI dJMbjb GdJfejI GdeSJOGeI(B. (3JgOa gPg GdOQGSI Edi GdJYQa Ydi QCi GdQjajGJ h JLQHJgf ai GdGdJMGb HaUhd eMh GdCejI(B: (3h OQGSI OhGaY GdeHMhKGJ ddEdJMGb HgPg HGdaUhd(B: (3h OQLI GSJaGOJgf efgG h cPdc GdJYQa Ydi CKQ GdfOhGJ GdoebOeI ef NdGd GdHQfGeL Ydi CSQgf h Jecjfgf(B. (3CLQjJ gPg GdOQGSI Ydi (B(210) (3GddGJi CJeef OQGSJgf HaUhd eMh GdCejI h MUdf Ydi GdTgGOI h bO Je GNJjGQgf YThGFjkG ef (B8 (3bQi ef eQcRi (B((3CHh GdfeQS h ChSje(B) (3ef eMGaXI GdLjRI(B: (3h Je LeY GdHjGfGJ GdejOGfjI GdNGUI HGdOQGSI ai OjSeHQ(B2017 (3HGSJNOGe GdWQjbI GdcejI HGSJNOGe GSJeGQI GdGSJHjGf HGdebGHdI GdTNUjI eY GdeHMhKGJ GddGJi MUdf Ydi TgGOI eMh GdCejI(B. (3Je GSJNOGe eQHY cGi dGNJHGQ eYfhjI GdaQhb ai JhRjY eaQOGJ GdYjfI Ydi aFGJ GdeJZjQGJ GdeSJbdI GdeOQhSI(B. (3h GSJNOe GdJMdjd GdYGedi ddhUhd Edi GdYhGed GdJi oJYHQ Yf OQLI GdGSJaGOI ef GdfOhGJ ai aUhd eMh GdCejI(B: (3ceG GSJNOe GdGfMOGQ GdoeJYOO dJMdjd eOi GSgGe cdG ef GdNUGFU GdTNUjI h GdGbJUGOjI h YhGed NGUI HGdHQfGeL h Hjf OQLI GdGSJaGOI ef GdfOhGJ h eOi Jecjf GdNQjLGJ HYO GfJgGA GdHQfGeLs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdRQGYI (B- (3bSe GdGLJeGY GdQjai h GdEQTGO GdRQGYis
(3UOQ GjVG cbQU eOeLs
Keywords: (3HQGeL eMh GdCejIs; (3JYdje GdcHGQs; (3Jecjf GdeQCIs